Laryngeal Neuroendocrine Carcinomas: A Retrospective Study of 14 Cases - Zhu, Yingying (Biomed Res Int, 2015)
Laryngeal neuroendocrine carcinomas (LNECs) are rare and highly heterogeneous which present a wide spectrum of pathological and clinical manifestations. Fourteen patients with histologically demonstrated LNEC were collected and analyzed retrospectively. The 14 cases were classified into 3 subtypes: typical carcinoid in 2, atypical carcinoid in 5, and small cell neuroendocrine carcinoma in 7. The mean survival time of the 14 patients in this study was 112.5 months (95% CI, 81.5–143.6). Surgeries were performed for 2 patients of typical carcinoid, and they were alive with no evidence of recurrence after 24 and 47 months of follow-ups. Patients in the atypical carcinoid group were treated with surgeries and postoperative radiotherapy. After 58.4 months of follow-ups (range: 9–144), 2 patients showed no evidence of disease and 1 was lost to follow-up after 72 months. The other 2 patients died of other unrelated diseases. In the small cell neuroendocrine carcinoma group, a combination of chemotherapy and radiotherapy was applied. The mean survival time was 79.7 months (95% CI, 37.9–121.4), and the 5-year survival rate was 53.6%. In conclusion, the clinical behaviors, treatment protocols, and prognosis are different for each subtype of LNECs.